Differences in ostracoda (crustacea) assemblages between two maar lakes and one sinkhole lake in the Konya region of Turkey - (:unkn) unknown (TUBITAK SCIENTIFIC & TECHNICAL RESEARCH COUNCIL TURKEY, 2008)
For this study, ostracod samples collected from a total of 9 stations in 2 maar lakes (Act and Meke) and 1 sinkhole lake (Meyil) in Konya, Turkey were investigated. Accordingly, 14 ostracod taxa (Darwinula stevensoni, Candona angulata, Candona sp. 1, Candona sp. 2, Pseudocandona marchica, Cypria sp., llyocypris gibba, 1. bradyi, 1. monstrifica, Heterocypris salina, Potamocypris sp., Limnocythere sp., Paralimnocythere sp., and Cythereis sp.) belonging to 10 genera were identified. Among them, only 2 species bradyi and P. marchica) were collected alive, while the others were found in sub-fossil form, and some shells of D. stevensoni were found containing soft parts. The 3 lakes were compared by species variety and population density, and the Meyil sinkhole lake was found to be richer than the Act and Meke maar lakes. The reason for this difference is thought to be the low level of salinity and the high level of oxygen in Meyil Lake.
Keywords: ostracoda; ecology; salinity; maar lake; sinkhole lake; turkey; BOLU; ECOLOGY; INDICATORS